Distributed asynchronous algorithms in the Internet – new routing and traffic control methods - Andrzej Karbowski (Journal of Telecommunications and Information Technology, 2005)
The paper presents several new algorithms concerning the third (network) and the fourth (transport) layer of ISO/OSI network model. For the third layer two classes of the shortest paths algorithms – label correcting and auction algorithms – are proposed. For the fourth layer an application of price decomposition to network optimization and Internet congestion control is suggested.